2016
DOI: 10.1038/srep32558
|View full text |Cite
|
Sign up to set email alerts
|

Joint estimation of preferential attachment and node fitness in growing complex networks

Abstract: Complex network growth across diverse fields of science is hypothesized to be driven in the main by a combination of preferential attachment and node fitness processes. For measuring the respective influences of these processes, previous approaches make strong and untested assumptions on the functional forms of either the preferential attachment function or fitness function or both. We introduce a Bayesian statistical method called PAFit to estimate preferential attachment and node fitness without imposing suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
90
0
13

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(111 citation statements)
references
References 60 publications
3
90
0
13
Order By: Relevance
“…where C(e) is the set of edges indistinguishable from e. We finally compute the correlation between τ * (e) and the ground truth, using Eq. (16). The resulting bound corresponds to the correlation we would have obtained had we known the true arrival time of edges, without the labeling of G.…”
Section: Inference On Artificial Treesmentioning
confidence: 86%
See 1 more Smart Citation
“…where C(e) is the set of edges indistinguishable from e. We finally compute the correlation between τ * (e) and the ground truth, using Eq. (16). The resulting bound corresponds to the correlation we would have obtained had we known the true arrival time of edges, without the labeling of G.…”
Section: Inference On Artificial Treesmentioning
confidence: 86%
“…At the level of detailed mechanisms, they have been shown to act effectively as generative models of complex networks [12,13], i.e., as stochastic processes that can explain the minutia of a network's growth [14,15]. This point of view has led, for example, to powerful statistical tests that can help determine how networks evolve and change [16,17].…”
mentioning
confidence: 99%
“…Equation 1 has a number of applications. Based on the functional forms of A k and η i , we can test for the presence of one and/or the other of the "rich-get-richer" and "fit-getricher" phenomena in a temporal network (Pham, Sheridan, and Shimodaira 2016). These two mechanisms have been advanced to explain another phenomenon called the "generalized friendship paradox" (Feld 1991;Eom and Jo 2014;Momeni and Rabbat 2015).…”
Section: Introductionmentioning
confidence: 99%
“…This model shall be compared to the physics-inspired predictive model developed by Wang, Song, and Barabasi [16]. Pham, Sheridan, and Shimodaira [36,37] developed a software package based on this model and demonstrated that it is a valid predictive tool. This model includes three paper-specific parameters: fitness η, immediacy µ, and σ.…”
Section: Discussionmentioning
confidence: 99%